ASPEK-ASPEK KESULITAN PESERTA DIDIK DALAM MEMAHAMI MATA PELAJARAN IPA DI KELAS V SDN PETAPA KECAMATAN PARIGI TENGAH KABUPATEN PARIGI MAUTONG - Nursetia Rini; karmawati karmawati; Rahmawaty Rahmawaty (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2021)
This study aims to determine the aspects of students' learning difficulties in science subjects in class V at SDN Petapa and to find out the teacher's efforts to overcome students' difficulties in understanding science subjects in class V at SDN Petapa. This type of research is descriptive research with a qualitative approach. The subjects in this study were 16 students with learning difficulties in science and class teachers. Data collection techniques using interview techniques, observation and documentation. The data analysis of this research used the Interactive Analysis Model. In obtaining the validity of the data, the researchers conducted a credibility and confirmability test. The results of this study indicate that aspects of students' difficulties in understanding science subjects consist of two aspects, namely internal aspects which include aspects of interest, motivation and self-readiness aspects of students. Next is the external aspect, namely school facilities, teachers and infrastructure. Meanwhile, the teacher's efforts in overcoming learning difficulties in science subjects are diagnosing learning difficulties with the aim of identifying the causes of learning difficulties.